O branding de uma professora "do rock": (des)construção de relações de privilégio, preconceito e o artístico - Raquel Cabral Pereira Boavista Carvalho (2023)
This internship report, in addition to serving as a teaching qualification in recruitment group of Visual Arts, aims to reflect on the position, space and time occupied by a teacher, questioning the subjective layers of privilege and prejudice that construct her and establishing relationships between these and the artistic. I begin by drawing a brief portrait of the occupation of leisure time with the artistic, questioning what that leisure time represents and how the artistic fills it. I talk about a woman-body that occupies the classroom and expose the weaknesses it is subjected to, which jeopardise intelligence, capacity and respect for this body. I introduce the didactic proposal presented in the Graphic Design and Communication Course, as part of my internship at Escola Artística e Profissional Árvore, as a critical and subversive exercise that aims to think about/question the place, position and action of graphic design(er). Based on this desire, I outline a brief state of the art on graphic design, exploring dimensions of privilege. In contrast to ideals of originality and creativity, it is considered an act of making, in the form of an ode to routine, starting from Descriptive Geometry classes. When reporting concrete experiences in the classroom, we reflect on the (de)construction of relations of prejudice and privilege and the way in which art surrounds and wanders among and around these social constructions. I end with an account of a "real" experience during the 2022/23 school year, reflecting on the relationships established and how dimensions of power condemn us to fall into salvationist rhetoric and plunge the artistic into a rhetoric of effects.